From Genes to Animal Behavior Social Structures, Personalities, Communication by Color - Inoue-Murayama, Miho.; Kawamura, Shoji; Weiss, Alexander; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2011)
The biological and genetic bases of behavioral diversity have long been topics of study within many disciplines, including evolutionary biology, genetics, ethology, sociobiology, and comparative psychology, but only relatively recently have attempts been made to bring these different approaches together. This volume covers a wide range of interdisciplinary research which uses some of the newest and most promising methods and technologies. Presented here is an overview of findings in the ongoing search for the ultimate causes of behavior in several different species, including primates, dogs, rodents, birds, and fish. Divided into five parts, the work describes research on sexual and kin selection, personality and temperament, molecular genetics of personality, color vision and body coloration, and the neurological underpinnings of complex behaviors. Valuable for researchers as well as graduate students in a wide range of fields from neuroscience to ecology, the book is also useful to those seeking to move beyond the boundaries of their own discipline and to expand their knowledge.
1-1 Female mate choice in rodents -- 1-2 Extra-Pair Copulations and the Strength of Sexual Selection in birds -- 1-3 Male reproductive skew and paternal kin-biased behavior in primates -- 1-4 Social structures and conflict resolution in primitively eusocial Polistes wasps -- 2-1 How to measure animal personality and why does it matter? Integrating the psychological and biological approaches to animal personality -- 2-2 Evolutionary genetics of personality in nonhuman primates -- 2-3 Towards a basis for the phenotypic gambit: advances in the evolutionary genetics of animal personality -- 2-4 Applications of personality to the management and conservation of nonhuman animals -- 2-5 Developing and validating measures of temperament in livestock -- 3-1 Personality-related genes in humans and model organisms -- 3-2 Molecular behavioral research in great apes -- 3-3 "Genetics and the social behaviour of the dog" revisited: Searching for genes relating to personality in dogs -- 3-4 Personality-associated genetic variation in birds and its possible significance for avian evolution, conservation and welfare -- 4-1 Evolutionary genetics of coloration in primates and other vertebrates -- 4-2 Speciation of cichlid fishes by sensory drive -- 4-3 Evolutionary diversification of visual opsin genes in fish and primates -- 5-1 The effect of endocrine disrupting chemicals on the development of macaque socialization -- 5-2 Functional association between brain and physiological responses accompanying negative and positive emotions and its regulation by genetic factors -- 5-3 Molecular Brain Imaging For Personality Traits in Non-Human Primates: A Study in the Common Marmoset.
Keywords: Life sciences; Animal genetics; Life Sciences; Animal Genetics and Genomics